Enhancement of methane production in anaerobic digestion process: A review - Li, Yue; Chen, Yinguang; Wu, Jiang (Applied energy, 2019)
[Display omitted] •Recent advances in increasing hydrolysis are introduced.•Strategies for enhancing enzyme activity relevant with VFA generation are reviewed.•Acceleration of direct interspecies electron transfer facilitates methanogenesis.•Improving methane production through special pathway is beneficial to anaerobic digestion.•Techno-economic assessment of approaches in the lab-scale is presented. With the increase of energy consumption and wastes generation due to human activities, anaerobic digestion (AD), a technology which turns wastes into bio-energy, is receiving more and more attention in the world. It is well known that there are at least three stages involved in anaerobic digestion, i.e., hydrolysis, acidification, and methanogenesis. Until now, however, the advances in enhancing acidification and methanogenesis have not been reviewed. This review provides a comprehensive overview of the methods reported to enhance each step involved in anaerobic digestion. More important, enzymes are the key to anaerobic digestion, and the strategies for improving enzyme activity are summarized. As electron transfer has been reported to play an important role in anaerobic digestion, the research progress of the approaches for the acceleration of direct interspecies electron transfer in methane production is also introduced. In addition, the recent advances in increasing the reduction of carbon dioxide to methane, which has been widely observed in methanogenesis step, are reviewed. Furthermore, the techno-economic assessment of anaerobic digestion is made, and the key points for future studies are proposed.